DEVELOPMENT OF SUSTAINABILITY BALANCED SCORECARD: IMPACT ON COMPANY PERFORMANCE AND IMPLEMENTATION - Hapsari, Dian Indriana; Chuang, Ya-Hsueh (Bina Nusantara University, 2025)
This study explores integrating sustainability principles into the Balanced Scorecard (BSC) by incorporating Environmental, Social, and Governance (ESG) indicators. The research identifies how ESG aspects can be systematically embedded within the BSC framework to enhance company performance, promote transparency, and strengthen corporate social responsibility. This study narrows its scope to companies within the manufacturing industry to ensure coherence, given its significant contribution to the national economy and environmental impact. The sample consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX), allowing for a more targeted application of the SBSC framework and relevant SULA indicators. These findings are expected to contribute to the practical and theoretical understanding of sustainability reporting and holistic performance measurement. Recognizing the fragmented and qualitative nature of prior sustainability performance assessments, this study introduces a holistic and data-driven framework using sustainability-linked accountability (SULA) indicators. The proposed model allows for standardized, cross-sector evaluation of ESG performance, particularly in the context of the Indonesian manufacturing industry. Based on literature analysis and empirical data, the study develops and applies a conceptual framework that integrates ESG metrics into BSC perspectives. The findings contribute to both theoretical advancement and practical implementation of comprehensive sustainability performance measurement systems.